PRINCIPLES OF THE ORGANIZATION OF EDUCATIONAL ACTIVITIES IN UKRAINIAN UNIVERSITIES LOCATED IN THE COMBAT ZONE - Voronko Vitalii; Voronovska Larysa (Alfred Nobel University Publisher, 2022)
The article examines the problem of organizing educational activities in Ukrainian universities located in the war zone. The purpose of the article is to highlight the principles of the organization of educational activities in such universities. It is noted that classical approaches to determining the principles of organizing educational activities in wartime require updating the content and emphasizing the psychological and security component of the educational process. The tasks of the research have determined the relevance of the problem of ensuring an admissibly effective educational process in universities that remained to work in the territories close to the front line, which is determined by the organization of training, on the one hand, with the provision of the necessary qualitative effectiveness and, on the other hand, the conditions of physical safety of the subjects of interaction being observed as far as possible (teachers and students). In the research, the methods of analysis of scientific sources, experience of Ukrainian universities located in the combat zone (Sumy, Kharkiv, Mykolaiv) have been used; generalization and systematization of the current work of lecturers in Kharkiv University in conditions of forced online learning and asynchronous communication have been applied. Research results. The scientific problem of the current state of the educational process in Ukrainian universities located in the war zone is defined. Firstly, taking into account not only the didactic component of the educational process, but also the psychological features of communication in war conditions, the emphasis is shifted to the preservation of the lives of the participants in the educational interaction, i.e. teachers and students, which prompts the teacher as the organizer of the class to take into account air raid sirens and provide students with the opportunity to descend into the bomb shelter. Secondly, the experience of Israeli colleagues regarding psychological switching from emotions to logic in life-threatening situations is taken into account, when a person who has received the impression of a crisis situation should not become its passive victim, but an active participant in solving the problem. Thirdly, the problem of preserving and maintaining the quality of education, which has worsened due to the impossibility of conducting classes in classrooms and energy instability, has been updated since, instead, the organization of the educational process takes place through online classes and communication in the asynchronous mode. There has been conducted the qualitative review of the content and forms of implementation of students' psychological relief by teachers, in particular through the discussion of critical emotional events, and encouraging students to be creative as a way of sublimating stress. Finally, the principle of informative efficiency is emphasized, which is manifested through the organization of communication between the subjects of educational interaction, the offer of variable forms of obtaining information (in synchronous and asynchronous mode), the involvement of students in relevant professional events organized mainly on a free basis, as well as the support of their cognitive activities in the form of consultations and discussions of modern trends.